COVID-19 disclosure: A novel measurement and annual report uncertainty - Mahmoud Elmarzouky; Khaldoon Albitar; Atm Enayet Karim; Ahmed Saber Moussa (Journal of Risk and Financial Management, 2021)
This paper provides a unique COVID-19 disclosure measurement and investigates the association between the level of COVID-19 disclosure and uncertainty within annual reports for UK FTSE-All share non-financial firms. We used automated textual analysis to score the sampled annual reports. The results show that the level of COVID-19 disclosure varies from industry to industry. Furthermore, there is a positive relationship between COVID-19 disclosure and uncertainty in annual reports. Firms with larger boards exhibit more significant uncertainty in annual reports with COVID-19 disclosure. However, the significance of uncertainty in annual reports with COVID-19 disclosure remains at the same level with different board independence percentages. The unique findings of this paper are extremely relevant to governments, shareholders, policymakers, suppliers, and creditors.
Keywords: 330; COVID-19 disclosure; annual report uncertainty; board size; independent directors; textual analysis